A random PWM control strategy for a three level inverter used in a grid connected photovoltaic system - Kamal Himour; K. Iffouzar (Institute of Advanced Engineering and Science, 2020)
The work presented in this paper is devoted to the control of a photovoltaic system connected to grid by a three level diode clamed inverter. A control structure based on three parts: dc link voltage control, power injected control and current control is proposed. In this work, the random PWM strategy is used to generate control signals for the multilevel inverter used us an interface to connect photovoltaic generators to the grid. Numerical simulations are performed using MATLAB / Simulink software, the simulation results for the proposed system indicate the performances of the proposed control structure, minimization of harmonics by the random PWM strategy applied and injection to the grid more active power by the multilevel inverter structure.